Research of the main advantages in social oriented accounting - Shkulipa, Ljudmyla (Technology audit and production reserves, 2017)
In the article, a correlation of restructuring industry processes with accounting in the common hot spot to safe a social component has been determined. A procedure of restructuring any industry is obtained as an initial question in its social oriented accounting. The manifestation the last one provides its key role for the economic analysis, the planning expenses for transfer infrastructure facilities, and actions aimed to social protection work community. As a result, any change at the time record have a necessity for certain changes in the accounting system. That is why, while the social component in the world economy is having its relevance, the national economy is needed not getting lost this component, especially at the moment those restructuring reforms in industry and rebuilding of the economy country, and contributing appropriate changes into accounting. The methods for socialization accounting have been proposed. They allow doing the accounting relevant, credible, open and motivating workers for the best industrial result. The social component is able to influence positively on the productive component and improve those results in which the owner is interested. Therefore, the social oriented accounting using high motivated and social secured workers is capable to help in reaching successful productive processes. Thus, thanks to the social oriented accounting, minimal expenses and the highest productive results at the same time can be obtained. Having comparative analysis the social differences between two accounting systems in such as the USSR and Ukraine, the main component in the social oriented accounting has been identified. It is a qualitative component, which is able to raise level of economic performance at all levels – both macro and micro. It called in the USSR like ‘a sign of quality’ and looked like a star including motivation to work. Therefore, it is considered that a government support for new accounting theories connected with a social responsibility and improvement of living population standards is required in nowadays.